PROFIL SEKUELE GANGGUAN NEUROBEHAVIOUR PADA PASIENdashPASIEN TRAUMA KEPALA POLIKLINIK FUNGSI LUHUR RSCM NOVEMBER 2008dashJUNI 2010 - Winnugroho Wiratman*,Sheila Agustini*, Yetty Ramli*, Silvia Lumempouw* (NEURONA, 2010)
INTRODUCTION TRAUMATIC BRAIN INJURY COULD CAUSE ATTENTION DEFICIT DISORIENTATION CONCENTRATION DISORDER DUE TO DIFFUSE INJURY AND ALSO COULD CAUSE IMPAIRED LANGUAGE SKILLS AND VISUOSPATIAL DISORDER DUE TO FOCAL LESION OTHER COGNITIVE DISORDERS CAUSED BY TRAUMATIC BRAIN INJURY ARE ALTERED ACADEMIC ABILITIES EXECUTIVE AND DECREASED MEMORY FUNCTIONING